Light manufacturing in Zambia : job creation and prosperity in a resource-based economy - Dinh, Hinh T., 1953- (World Bank e-Library., 2013)
"This book argues that light manufacturing is appropriate for a resource-based country like Zambia. While Zambia's recent growth has been impressive, it has not been accompanied with adequate job creation. Long-term job creation in copper production is very small; links to the rest of the economy tend to be weak as well. Besides, the development of natural resources tends to discourage job-creating sectors such as manufacturing. To be sustainable and to create productive employment for its people, growth needs to be accompanied by structural transformation. Such transformation entails a growing share of manufacturing output in the economy. In the past, Zambia's efforts to promote and facilitate industrial growth have not been very successful. Policy regimes swung from one extreme to another. In the 1980s, Zambia put complete control of the industrial sector in the hands of the state. When this model proved unsuccessful, policy shifted in the opposite direction in the 1990s, and all earlier government interventions were lifted. Neither extreme led to sustained growth of manufacturing. This book suggests an alternative: directing government policies toward removing constraints in a few of the most promising light manufacturing sectors using practical and innovative solutions inspired by the fast-growing Asian economies whose starting point 20 years ago was not very different from Zambia's today. This book has several innovative features. First, it provides in-depth cost comparisons between Zambia and four other countries in Asia and Africa at sector and product levels. Second, the book uses a wide array of quantitative and qualitative techniques to identify key constraints to enterprises and to evaluate differences in the performance of firms across countries. Third, it uses a focused approach to identify country- and industry- specific constraints. It proposes markett based measures and selected government intervention to ease these constraints. Fourth, it highlights the interconnectedness of constraints and solutions. For example, solving the manufacturing input problem requires actions in agriculture, education, and infrastructure. The book shows that Zambia has the potential to become regionally competitive in several light manufacturing subsectors by leveraging its comparative advantage in natural resource industries such as agriculture, livestock, and forestry. Interventions include both the provision of public goods and the removal of existing policy distortions in the economy. Growing production of light manufacturing goods would allow Zambia to capture more value from its raw materials and create more jobs."--Publisher's website.